Teaching Mathematics Meaningfully, 2e : Solutions for Reaching Struggling Learners, Second Edition. - Allsopp, David (Brookes Publishing, 2018)
In the new edition of Teaching Mathematics Meaninfully, the authors have incorporated current research, aligned concepts and practices with the Common Core State Standards and NCTM teaching practices, explained learning trajectories in mathematics, and discussed how to use their instructional process within RTI/MTSS. Based on a foundation of identifying and understanding the Mathematics, the authors' conceptual framework integrates continuous assessment and two perspectives, math learning needs and the learning needs of struggling learners, to plan and implement responsive instruction.